(untitled) (Research, Society and Development, 2021)
To analyze the association between socio-demographic factors and lifestyle in Salvadoran quilombola adults with disabilities, 517 face-to-face interviews were considered. Binary logistic regression was performed to define the association between Lifestyle and sociodemographic factors. Schooling remained associated with Nutrition, Income to Physical Activity, Number of Children with Preventive Behavior and Relationships, and Sex with Stress. Therefore, having less schooling increases the likelihood for negative nutrition, having higher income increases the likelihood for positive physical activity. Having more children increases the likelihood of Preventive Behavior and Positive Relationships and being man to Positive Stress.